Acromioclavicular joint mobilizations for the management of grade I sternoclavicular joint sprain: a case report - Helvey-Byers, Rosemary; O’Laughlin, Jeffrey; Dickson, Nicole; Myer, Reuben; Gross, Michael (Physiotherapy theory and practice, 2024)
Injury to the sternoclavicular joint is a rare phenomenon that has implications for the shoulder complex. Limited literature exists on optimal physical therapy rehabilitation after a sternoclavicular ligament sprain. This case report details the physical therapy management and outcomes of a patient with a posterior sternoclavicular joint sprain. The patient was a 34-year-old female who sustained a grade I posteriorly directed sternoclavicular sprain during a motor vehicle accident. She received a combination of acromioclavicular joint mobilizations and therapeutic exercise for her shoulder complex for five sessions over six weeks. At discharge, the patient surpassed the minimally clinically important difference (MCID) and the minimal detectable change (MDC) in her Quick-DASH score. She surpassed the MDC and MCID in her Numerical Pain Rating Scale score. She was able to regain full functional use of her involved upper extremity and returned to her work and original exercise regimen with no further limitations. The outcomes suggest that a combination of acromioclavicular joint mobilizations and therapeutic exercise for the shoulder complex was a suitable option for the conservative management of this patient's grade I sternoclavicular sprain.